Patterns and drivers of Holocene moisture variability in mid-latitude eastern North America - J. Sakari Salonen; Frederik Schenk; John W. Williams; Bryan Shuman; Ana L. Lindroth Dauner; Sebastian Wagner; Johann Jungclaus; Qiong Zhang; Miska Luoto (Nature Communications)
Abstract Proxy data for eastern North American hydroclimate indicate strong and persistent multi-millennial droughts during the Holocene, but climate model simulations often fail to reproduce the proxy-inferred droughts. Diagnosing the data–model mismatch can offer valuable insights about the drivers of hydrological variability and different regional sensitivities to hydroclimate forcing. Here we present a proxy–modeling synthesis for Holocene climates in the eastern North American mid-latitudes, including machine-learning-based water balance reconstructions and high-resolution climate simulations. These data-model results resolve prior-generation inconsistencies, show consistent spatiotemporal patterns of Holocene hydroclimate change, and enable assessment of the driving mechanisms. This agreement suggests that the secular summer insolation trend, combined with the Laurentide Ice Sheet deglaciation and its effect on atmospheric circulation, together explain the extent and duration of drier-than-present climates. In addition, our high-resolution proxy data and transient simulations reveal clear multi-centennial climate variability. In our simulations, temperature-driven increases in evapotranspiration exceed regional precipitation gains, drying much of the region during the mid Holocene. This suggests that the mid-Holocene multi-millennial drought was driven by similar processes compared to the drying trajectory projected for mid-latitude North America over this century, which is also primarily driven by warming.